Social determinants of health and dental caries in Brazil: a systematic review of the literature between 1999 and 2010 - Antonio Fernando Boing; João Luiz Bastos; Karen Glazer Peres; José Leopoldo Ferreira Antunes; Marco Aurélio Peres (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: To review epidemiological studies conducted in Brazil that investigated the distribution of dental caries according to socioeconomic status and demographic characteristics. METHODS: The systematic review included articles published between 1999 and 2010 available in six bibliographic sources, without any other restriction. We analyzed the bibliometric and methodological characteristics of the studies, and the direction and statistical significance of associations tested. RESULTS: Of the 1,128 references identified, 67 were incorporated into this study. There was a higher percentage of publications in the last two years and most of the studies were conducted in the South and Southeast of the country with a young population. The cross-sectional design, using a complex sampling procedure, was the most commonly adopted. The DMFT and dmft indexes were the most commonly used to measure dental caries, while sex/gender, income, education, race/skin color and type of school were the most common socioeconomic exposures. CONCLUSIONS: Most studies identified a high rates of dental caries among the poorest, least educated, black and brown and female individuals. A more detailed methodological and theoretically sound study of the relationship between dental caries and socioeconomic conditions is needed.